Thermostability and regulation of Clostridium thermocellum L-lactate dehydrogenase expressed in Escherichia coli - (:unkn) unknown (SPRINGER, 2005)
In this study, L-lactate dehydrogenase (L-LDH) of Clostridium thermocellum previously cloned aid expressed in Escherichia coli FMJ39 was partially purified and characterised. Optimum temperature and pH of the enzyme were found as 50 degrees C and 7.5, respectively. Different concentrations of Mn2+ did not affect the enzyme activity. Addition of 20-30 mM Mg2+, or the other hand, increased the LDH activity by about 10%. Relatively high concentrations of NaCl (2 M), fructose-1,6-diphosphate (FDP, 5 mM), ATP (10 mM) and NAD (40 mM) decreased LDH activity by 36, 25, 40 and 100%, respectively. Oxamate and oxalate inhibited LDH activity by 41 and 28%, respectively, when each was added at a concentration of 0.5 mM. When compared to its non-thermotolerant counterparts, the enzyme was found to be very stable when incubated at room temperature, 4 degrees C and even at 50 degrees C.
Keywords: Clostridium thermocellum; L-lactate dehydrogenase; L-lactate; thermostability; enzyme stability; LACTIC-ACID DEHYDROGENASES; LACTOBACILLUS-HELVETICUS; PURIFICATION; GENE; ACETOBUTYLICUM; LEUCONOSTOC; ENZYME; ACTIVATION; KINETICS; BACILLUS